Diseño de un simulador de choque frontal de un vehículo para la empresa Cinfovial (2018)
For the realization of the present project, a study and analysis of the frontal shock simulators present in different markets was carried out, to know the operation models and functional characteristics; then, the basic parameters and functional requirements were established, which were supplied by the CINFOVIAL company, including technical specifications, design and geometry of the mechanism, among others. Based on the requirements and operating parameters, a conceptual design was proposed, giving way to the evaluation of three alternatives for the reel acceleration system, from which the one corresponding to gravity acceleration by inclined plane was selected. Once the alternative was selected, the detailed design of the structure and the selection of the different systems that make up the simulator were made. The modeling and manufacturing plans of the structure and its systems were carried out, using CAD software, to later analyze in a specific way the critical elements of the fixed and mobile metal structure through the finite element method. Design completed; The financial evaluation of the project was carried out, which was developed around the variables TIO and VPN. Finally, the environmental impact assessment of the project was carried out and the assembly, operation and maintenance manuals of the simulation were designed.